Biliary excretion of pravastatin and taurocholate in rats with bile salt export pump (Bsep) impairment. (20th July 2016) - Cheng, Yaofeng; Freeden, Chris; Zhang, Yueping; Abraham, Pamela; Shen, Hong; Wescott, Debra; Humphreys, W. Griffith; Gan, Jinping; Lai, Yurong
Abstract: The bile salt export pump (BSEP) is expressed on the canalicular membrane of hepatocytes regulating liver bile salt excretion, and impairment of BSEP function may lead to cholestasis in humans. This study explored drug biliary excretion, as well as serum chemistry, individual bile acid concentrations and liver transporter expressions, in the SAGE Bsep knockout (KO) rat model. It was observed that the Bsep protein in KO rats was decreased to 15% of that in the wild type (WT), as quantified using LC–MS/MS. While the levels of Ntcp and Mrp2 were not significantly altered, Mrp3 expression increased and Oatp1a1 decreased in KO animals. Compared with the WT rats, the KO rats had similar serum chemistry and showed normal liver transaminases. Although the total plasma bile salts and bile flow were not significantly changed in Bsep KO rats, individual bile acids in plasma and liver demonstrated variable changes, indicating the impact of Bsep KO. Following an intravenous dose of deuterium labeled taurocholic acid (D4‐TCA, 2 mg/kg), the D4‐TCA plasma exposure was higher and bile excretion was delayed by approximately 0.5 h in the KO rats. No differences were observed for the pravastatin plasma concentration–time profile or the biliary excretion after intravenous administration (1 mg/kg). Collectively, the results revealed that these rats have significantly lower Bsep expression, therefore affecting the biliary excretion of endogenous bile acids and Bsep substrates. However, these rats are able to maintain a relatively normal liver function through the remaining Bsep protein and via the regulation of other transporters. Copyright © 2016 John Wiley & Sons, Ltd.